Rethinking professional issues in special education - Paul, James L. (Contemporary studies in social and policy issues in education., 2002)
Special educators are facing new challenges at the beginning of the 21st century as public education is being reformed by a vision focusing on measurable student outcomes. The future course of the field will be shaped by the policy and programmatic responses to several issues, including demographic changes in student populations, a lack of certified special education teachers, criticism in the public media for the rising costs of services, and debates about the preferred philosophy of service delivery for students with disabilities. Additional chapters discuss university-school collaboration, charter schools, disability studies, school violence, disproportionality in placement, male African-American teachers, and ethics.